Pemikiran Ahmad Mustain Nasoha Tentang Relasi Konstitusi dan Syariat Islam dalam Perspektif Kewarganegaraan Indonesia - Riyana Akhsani; Annisa Nur Husna; Nada Fatma; Yunifa Rihhadatul ‘Isyiyah; Ardhita Juliani Ardhani (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study examines Ahmad Mustain Nasoha’s thoughts on the relationship between the constitution and Islamic law (sharia) within the context of Indonesian citizenship. The interaction between religion and the state in Indonesia has always been a dynamic discourse, particularly in balancing Islamic values as the majority religion with the constitutional principles rooted in Pancasila and the 1945 Constitution. This research employs a qualitative method using a literature review approach to analyze Nasoha’s works and perspectives on integrating Islamic values into the legal and state systems. The findings reveal that, according to Nasoha, Islamic law should not be formalized in a legalistic manner but should function as a moral inspiration and social norm within national life. Through the perspective of legal syncretism, Islamic law, customary law, and national law can be harmonized to create an inclusive and just legal system. Pancasila serves as a meeting point that bridges religious and constitutional principles, allowing Muslims to practice Islamic teachings without conflicting with the constitution. Nasoha’s thought offers a moderate and contextual model of citizenship suitable for Indonesia’s pluralistic society.